Claspin overexpression is associated with high‐grade histology and poor prognosis in renal cell carcinoma. Issue 3 (3rd February 2020) - Kobayashi, Go; Sentani, Kazuhiro; Babasaki, Takashi; Sekino, Yohei; Shigematsu, Yoshinori; Hayashi, Tetsutaro; Oue, Naohide; Teishima, Jun; Matsubara, Akio; Sasaki, Naomi; Yasui, Wataru
Abstract: Renal cell carcinoma (RCC) is one of the most common human cancers. We previously reported that claspin is a key regulator in the progression of gastric cancer, and it likely plays an important role in cancer stem cells of gastric cancer. However, the significance of claspin in RCC has not been examined. First, we analyzed the expression and distribution of claspin in 95 RCC cases by immunohistochemistry. In the nonneoplastic kidney, the staining of claspin was either weak or absent, whereas RCC tissue showed nuclear staining. In total, claspin expression was detected in 45 (47%) of 95 RCC cases. The claspin staining appeared relatively stronger in high nuclear grade RCC than in low nuclear grade RCC. Claspin‐positive RCC cases were associated with higher T grade, tumor stage, nuclear grade, vein invasion, and poorer prognosis. CLSPN siRNA treatment decreased RCC cell proliferation. The levels of phosphorylated Erk and Akt were lower in CLSPN siRNA‐transfected RCC cells than in control cells. In addition, claspin was coexpressed with CD44, epidermal growth factor receptor, p53, and programmed death ligand‐1. These results suggest that claspin plays an important role in tumor progression in RCC and might be a prognostic marker and novel therapeutic target molecule. Abstract : The present study is the first detailed analysis of claspin expression in renal cell carcinoma (RCC) including its clinicopathological significance and biological function. Our investigation showed that claspin plays an important role in tumor progression in RCC and might be a prognostic marker and novel therapeutic target molecule.